Application For Determining The Best Tourism In Jombang District Using The Weighted Product Method Based On Android - Fadillah, Siti Nur; Sufaidah, Siti (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to develop an Android application that uses the Weighted Product (WP) method to determine the best tourist destinations in Jombang Regency. In today's digital era, the need for applications that can help tourists in choosing tourist destinations that suit their preferences and needs is increasing. The Weighted Product Method was chosen because of its ability to evaluate and give weight to various factors that affect tourist satisfaction, such as natural beauty, supporting facilities, accessibility, and safety. This research follows a systematic approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The analysis stage includes identifying user needs, analyzing system requirements, and determining evaluation criteria. Furthermore, an application design that considers a friendly and functional user interface is created based on the results of the previous analysis. Application development is carried out by utilizing various latest technologies in Android software development. Application implementation involves trials using data on tourist destinations in Jombang Regency to test the effectiveness and accuracy in determining the best tourist destinations. Evaluation is done through feedback from users and analysis of comparison results between destination recommendations provided by the application and user preferences. It is expected that the results of this research will not only make a positive contribution to tourism development in Jombang Regency by improving the quality of service to tourists, but also become a foundation for further research in the development of similar applications using the Weighted Product Method.